6-(1+2k)=-(k-1)

Simple and best practice solution for 6-(1+2k)=-(k-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-(1+2k)=-(k-1) equation:


Simplifying
6 + -1(1 + 2k) = -1(k + -1)
6 + (1 * -1 + 2k * -1) = -1(k + -1)
6 + (-1 + -2k) = -1(k + -1)

Combine like terms: 6 + -1 = 5
5 + -2k = -1(k + -1)

Reorder the terms:
5 + -2k = -1(-1 + k)
5 + -2k = (-1 * -1 + k * -1)
5 + -2k = (1 + -1k)

Solving
5 + -2k = 1 + -1k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add 'k' to each side of the equation.
5 + -2k + k = 1 + -1k + k

Combine like terms: -2k + k = -1k
5 + -1k = 1 + -1k + k

Combine like terms: -1k + k = 0
5 + -1k = 1 + 0
5 + -1k = 1

Add '-5' to each side of the equation.
5 + -5 + -1k = 1 + -5

Combine like terms: 5 + -5 = 0
0 + -1k = 1 + -5
-1k = 1 + -5

Combine like terms: 1 + -5 = -4
-1k = -4

Divide each side by '-1'.
k = 4

Simplifying
k = 4

See similar equations:

| 53a-14=63a+32 | | 9=-x+10 | | 6n-9=39 | | 40=25+20m | | 8y-x=8 | | 3x+8=-3+4x | | =-15-8(9d-16) | | 8(a^2-49)=0 | | -4(5+k)=-(k-1) | | -7y^4(5y^2+6y-8)= | | 7v+7v=0 | | 6(3x-0.4)=9x-2.4 | | 8-6x=-4x+6 | | 0.5-(-x+3)=x-5 | | 15=-x+10 | | -7v+7v=0 | | 30=2k+14 | | 1.1x+4.7=0.6x+4.4 | | 6x+6=x+26 | | (-75)=y+4y+25 | | 17x+66+11x=-10+x | | 4g+3(-6+4g)=1-9 | | -5(11-2x)-3y=-6 | | 2z+33=17 | | 26y-12=18y+12 | | 6(c-4)=3(s+9) | | 2b+9=188 | | 4(4x-4)+40=9x+3 | | 40.06=8g+3.58 | | 8(5y-3)3.2=x | | -4=-8n+8n | | 45+9x=-14 |

Equations solver categories